Demolishing the Present to Sell off the Future? The Emergence of 'Financialized Municipal Entrepreneurialism' in London. (7th May 2018) - Beswick, Joe; Penny, Joe
Abstract: This article introduces a new mode of urban entrepreneurialism in London through a study of the state‐executed, speculative development and financialization of public land. In response to an intensifying housing crisis and austerity‐imposed fiscal constraints, municipalities in London are devising entrepreneurial solutions to deliver more housing. Among these 'solutions' can be found the early signs of the state‐executed financialization of public housing in the UK with the use of speculative council‐owned special purpose vehicles (SPVs) that replace existing public housing stock with mixed‐tenure developments, creating ambiguous public/private tenancies that function as homes and the basis for liquid financial assets. Drawing together parallel literatures on the financialization of urban governance and housing, and combining these with original empirical research, we situate these developments in contrast to earlier modes of governance, identifying a distinct mode of entrepreneurial governance in London: financialized municipal entrepreneurialism . The local state is no longer merely the enabler—limited to providing strategic oversight of the private sector—but financializes its practice in a reimagined commercialized interventionism, as property speculator. This article concludes that while the architects of this new mode of entrepreneurialism extol the increased capacity and control it provides, any such gains must be set against longer‐term financial, democratic and political risks.